Optimizing Learning: Applying the Pomodoro Technique in Islamic Education - Rafliyanto, Muhammad; Mukhlis, Fahrudin (el-Tarbawi, 2023)
This research is motivated by students' difficulties in comprehending the material provided by educators. Among the contributing factors is the educators' lack of innovation in designing instruction. Students struggle to grasp the subject matter due to the instructors' abilities not being fully utilized in the design of teaching methods. This study seeks to demonstrate how the Pomodoro learning method is employed within the framework of official education guidelines for teaching Islamic religion. The research is conducted as a field study utilizing descriptive qualitative research techniques. The locus of the study is the Muhammadiyah Islamic Vocational High School (SMK) 2 Malang. Data collection for this study is carried out through observation, interviews, and documentation. The method of data analysis consists of data reduction, presentation, and drawing conclusions. The findings of this study depict that the Pomodoro learning technique is a time-management oriented approach, thereby ensuring that the concentration level of the students' learning remains undisturbed. This learning technique requires habitual practice to enable students to regulate their study time effectively.